Penyuluhan Pemahaman Layanan Informasi Tentang Studi Lanjut - Ani Endriani; Farida Herna Astuti; Diah Lukitasari; Dewi Rayani (Jurnal Pengabdian UNDIKMA, 2020)
This community service activity aims to equip children with various kinds of knowledge about further study, have a view on further study so that students are able to make decisions in choosing and planning their studies, according to their talents and interests. The method used in this service activity is counseling with lectures and open discussions in conveying material, this can facilitate the extension process and students are more flexible to ask questions about various matters related to further study. The target of this community service activity is the students of class XII SMA Negeri 1 Labuapi, West Lombok, totaling 30 students. The result of this service activity is that students are able to plan and make further study decisions they want after graduating from high school that is tailored to their talents and interests.